Proposta de controle pré-programado aplicado ao conversor Boost PFC sem sensor de corrente - Finazzi, Antonio de Pádua (2011)
The development of front-end converters for power factor correction and DC link voltage control of electronics converters such as, UPS, Inverters, and Switched Power Supplies, has been attracting great interest from the scientific community that works toward the achievements of cost reduction, high efficiency, and reliability. In this context, this paper proposes an innovative micro processed control technique for sinusoidal input line current imposition of front-end sensorless Boost converters, named in this work as BOOST-PFC-SSC. The proposed method is based on experimental acquisition of sequences of gate-to-source signals for different load conditions. These signals correspond to a complete cycle of the AC input voltage and are recorded in the microcontroller memory in order to be reproduced when used in a Boost converter, eliminating thus the use of a current sensor and predictive operations each switching interval, simplifying the control module executor. Aiming to prove the proposed digital concept, a 600W Boost-PFC-CSL was built and analyzed in laboratory and the main experimental results are presented herein.